FADING VALUES: ANALISIS MEMUDARNYA NILAI-NILAI PANCASILA DALAM INTERAKSI SOSIAL MASYARAKAT PERKOTAAN DI ERA MODERN - Teja Br Bukit , Hanna; Smith Panggabean , Rahel; Oliviena br Manurung , Rachel; Fitri Andini Br Siahaan , Wulan; Napitupulu , Esrawati; Gabriel Siahaan, Parlaungan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social changes in urban communities influenced by globalization and the development of digital technology have caused a shift in the application of Pancasila values, particularly in social interactions, which tend to be increasingly individualistic. This phenomenon creates a gap between the normative values of Pancasila and social practices in everyday life. This study aims to analyze the fading of Pancasila values, understand how society interprets these values, identify the factors influencing them, and examine their reception in the context of modern life. This research used a qualitative approach with a case study conducted in Kesawan Village, West Medan District. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that Pancasila values have not disappeared but have undergone a transformation into a more flexible and contextual form. This shift is evident in social practices such as mutual cooperation (gotong royong), which have begun to shift to digital forms. The interpretation of values is influenced by technological developments, modernization, and society's increasingly critical mindset. Furthermore, public reception of Pancasila values is dominated by a negotiated position, accepting the values but adapting them to the demands of modern life. Therefore, strengthening efforts are needed to ensure that Pancasila values remain relevant and can be effectively implemented in urban communities.